7 - Locked-in Metaphorically: The War on Hawking in Nairobi’s CBD and the Cat-and-Mouse Game - Wangui Kimani, Esther; Gachigua, Sammy Gakero; Kariuki, George Mbugua (Africa Development, 2020)
This article investigates how hawking in the streets of the Nairobi Central Business District (CBD) produces political spaces where processes related to belonging, inclusion and exclusion are played out and contested at both discursive and material levels. The article adopts the Conceptual Metaphor Framework to critically evaluate the conceptualisation of hawkers and hawking in Nairobi’s CBD by varied actors. The study finds that two dominant metaphors – the ‘war’ metaphor and the ‘cat-and-mouse’ metaphor – have persistently and resiliently defined the life-world of hawkers in the CBD and the hawkers’ relations with the City authorities. Further, that this conceptualisation has had adverse consequences, including providing a false clarity to this social phenomenon, which dehumanises the hawkers as well as naturalising and justifying the antagonistic relations between them and the authorities, thereby limiting the effective management of hawking within the CBD. The article concludes that there is a need for a revisionary framing of both the hawking phenomenon and the hawker-city-authorities relationship to facilitate broadened and progressive strategies and policies that would impact more positively on the material world of the hawker in the city.